The accessibility shift: Conceptual obstacles and how to overcome (one of) them - Jonathan C. Levine (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2020)
This paper explores conceptual barriers to shifting the foundation of transport planning from mobility to accessibility. These barriers include an implicit belief that accessibility must bring other benefits to be of value, the idea that individuals' failure to minimise costs in their transport choices somehow challenges the derived nature of transport demand; and a lack of techniques for project-level accessibility analysis. The paper also presents a technique for overcoming the latter barrier.
Keywords: 330